Potential Of Modified Gambir As Adsorbent For The Removal Of Selected Heavy Metal Ions From Aqueous Solutions - Tong, Kim Suan (2014)
In this study, gambir extracted and gambir pulp has been chemically modified with formaldehyde (FGA) and hydrochloric acid (AGPA), respectively. Adsorbents were physically and chemically characterized by FTIR, BET, TGA, SEM, EDS and pHpzc. The surface of FGA was found to be granular and honeycombed shape while AGPA was in spherical and compacted shape. The pHpzc values for FGA and AGPA were found to be 3.90 and 3.62, respectively. Hydroxyl (-OH) and carboxyl (-COOH) groups were detected by FTIR. The effects of pH, adsorbent dosage, initial concentration, contact time and temperature on adsorption were studied. The optimum conditions of pH for metal ions adsorption onto both FGA and AGPA were found to be pH 5.0 (Cu2+, Pb2+ ions) dan pH 6.0 (Ni2+, Co2+ ions), respectively. Meanwhile, the optimum conditions of adsorbent dosage for metal ions adsorption onto FGA were found to be 6.00 g/L (Cu2+ ions), 10.00 g/L (Pb2+ ions), 16.00 g/L (Ni2+, Co2+ ions) and for AGPA were found to be 10.00 g/L (Pb2+ ions), 12.00 g/L (Ni2+ ions), 16.00 g/L (Cu2+, Co2+ ions), respectively. The initial adsorption process was rapid and reached equilibrium within 90 min for all metal ions. Four types of kinetic models were applied to analyze kinetic data particularly pseudo-first order, pseudo-second order, Elovich and intraparticle diffusion. Pseudosecond order was found to be the best model that fitted well the kinetic data and predicted that chemisorptions took place in the process. Meanwhile, the intraparticle diffusion stated that there was more than one diffusion process as in this study.